Parentsâ Perception on Early Childhood Social Interaction Ability Viewed from Competitive Sports in Semarang Sport Clubs - Yanuar Rini, Rizky (BELIA: Early Childhood Education Papers, 2017)
Individual competitive sport club that children participate in make the level of their competitiveness increased. Children are required always compete and win until the emphasis on victory is often by the tendency to apply the concept of win by all means that can affect the development of children social interaction. The purposed of this research is to know the image of early childhood social interaction capability that participated in badminton, inline skate, swimming, taekwondo, and gymnastic club in Semarang based on parentsâ perception. Research method in this study used quantitative research with comparative approach. The subject of this research is 95 parents of 4-6 years children that participate in competitive sport club in Semarang and also domiciled in Semarang. Quota sample is used as sampling technique. Total of subject obtained is 45 people consisted of 9 parents of badminton athletes, 9 parents of inline skate athletes, 9 parents of swimming athletes, 9 parents of taekwondo athletes, and 9 parents of gymnastic athletes. Scale of early childhood social interaction ability is used as data collection tool whereas F-test is used as data analysis. Resulted of the research based on statistical calculation shows F calculated 1,421 whereas F table 0,61 which mean F calculated < F table (1,421 < 2,61) and p value > 0,05 which is 0,245 (0,245 > 0,05) which means there is no difference of early childhood social interaction ability based on sports club. Based on the research results can be conclude that there were 2 sport club with social interaction ability at a medium level and that was badminton with the mean score was 101,33 and inline skate with the mean score was 109,44. Then there were 3 sport clubs with social interaction ability at a hight level and that was swimming club with the mean score was 112,33, taekwondo with the mean score was 112,67 and gymnastic with the mean score was 114,11.